Descortinando os efeitos positivos e colaterais negativos das práticas agrícolas: um estudo exploratório descritivo de suas evoluções - Mokfa, Samuel Amorim (2025)
To claim that the history of humanity is exclusively the history of agriculture would be presumptuous. However, this may very well be the reality of the last twelve thousand years. Although the benefits of agriculture are undeniable, the relationship between it and planetary health proves to be complex and multifaceted. This paper sought to analyze its evolution, dividing it into five historical periods, listing, in each of them, both the positive effects and the negative side effects produced by humans through agricultural practices. To do so, a qualitative methodology was used, based on a narrative and critical review in an exploratory and descriptive manner. Throughout the different analyzed periods, a recurring pattern was identified: as societies become denser, more numerous, complex, and interdependent, agricultural practices tend to intensify, creating a cycle that is difficult to break. This intensification allowed for a significant increase in the production of food, goods, and byproducts, enabling substantial improvements in various socioeconomic aspects, as it formed the foundation for addressing social demands in different areas and eras. Its latest evolution brought with it intensive land and water use, large-scale application of chemicals and inorganic products, and ecological simplification. The (un)sustainability of this model is one of the greatest contemporary concerns, given that environmental degradation and ecological imbalances undermine the conditions that make agriculture possible. However, a deeper understanding can be gained by analyzing this facet, observing the apparent inseparability of this productive system in relation to increasingly dense and numerous societies, considering their economies, social patterns, and consumption decisions. In this regard, finding productive alternatives that balance the cause-and-effect relationships of agricultural activities with planetary health becomes challenging, given that social and economic nuances often hinder the implementation of environmentally sustainable agricultural practices. Finally, the research emphasizes that, to provide significant improvements and overcome contemporary challenges, it is essential to have a convergence of efforts from various fields of knowledge, as well as active participation from society as a whole.